2020
DOI: 10.5483/bmbrep.2020.53.2.059
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0075828 Promotes Bladder Cancer Cell Proliferation Through Activation of CREB1

Abstract: Circular RNAs (circRNAs), one kind of non-coding RNA, have been reported as critical regulators for modulating gene expression in cancer. In this study, microarray analysis was used to screen circRNA expression profiles of bladder cancer (BC) 5637 cells, T24 cells and normal control SV-HUC-1 cells. The data from the microarray showed that hsa_circ_0075828 (named circCASC15) was most highly expressed in 5637 and T24 cells. circCASC15 was highly expressed in BC tissues and cells. Overexpression of circCASC15 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…The luciferase reporter assay con rmed that hsa_circ_0089153 sponged hsa-miR-145 to mediate upregulation of ZEB2 expression, thereby playing a carcinogenic role in PTC. hsa_circ_0089153 was also reported to be upregulated in gastric cancer and bladder cancer [25,26]. Our study indicated that upregulated hsa_circ_0089153 may sponge hsa-miR-139-3p, and upregulated SPC24 and CDKN2A expression to promote PTC progression.…”
Section: Discussionmentioning
confidence: 59%
“…The luciferase reporter assay con rmed that hsa_circ_0089153 sponged hsa-miR-145 to mediate upregulation of ZEB2 expression, thereby playing a carcinogenic role in PTC. hsa_circ_0089153 was also reported to be upregulated in gastric cancer and bladder cancer [25,26]. Our study indicated that upregulated hsa_circ_0089153 may sponge hsa-miR-139-3p, and upregulated SPC24 and CDKN2A expression to promote PTC progression.…”
Section: Discussionmentioning
confidence: 59%
“…Because clinicopathological characteristics affect the prognosis of patients and circRNAs are closely related to the clinicopathological characteristics of BC, circRNAs may also be related to the prognosis of patients. Cumulative studies have confirmed that circ-BPTF, circTFRC, circZFR and circCASC15 are associated with overall survival in patients with BC; 27,28,30,34 circZFR, circPRMT5 and circCASC15 are associated with diseasefree survival; 30,31,34 and hsa_circ_0137439 is associated with recurrence-free survival and overall survival. 35 In general, higher levels of these circRNAs are associated with less favorable patient survival.…”
Section: Relationships Between Circrnas and Clinicopathological Charamentioning
confidence: 93%
“…Further analysis showed that high levels of these circRNAs are closely related to the clinicopathological stage of BC, which describes the tumor status, including the tumor size, presence of local and distant metastasis, and tumor pathological grade, and affect the survival of BC patients. [27][28][29][30][31][32][33][34] Regarding tumor tissue classifications, the levels of circRNAs, including circ-BPTF, circTFRC, circZFR, circPTK2, and circASXL1, were found to be significantly higher in low-grade BC tissues than in high-grade BC tissues. 27,28,30,32,33 Regarding the pathological TNM stage, circRNAs, including circTFRC, circZFR, circPRMT5, circPTK2, circASXL1 and circCASC15, were positively correlated with the T stage when patients were stratified into Ta-1 and T2-4 subgroups.…”
Section: Relationships Between Circrnas and Clinicopathological Charamentioning
confidence: 99%
See 2 more Smart Citations